Kajian Literatur Kurikulum E-sport dan Perkembangan Industri Game - Harya Bima Dirgantara; Tedi Lesmana Marselino; Yulia Ery Kurniawati (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The rapid development of the game industry has made games a part of today's life. Games that were used only as entertainment have penetrated into the field of sports, which is called e-sport. E-sport has also begun to develop in Indonesia, as evidenced by the presence of several e-sport teams and professional competitions in Indonesia. In this proposal, the development of an e-sport curriculum is proposed. The goal is for an organization/industry body/school that views e-sports as a new sports culture and is ready to support and whenever possible participate in developing prospective e-sport athletes to be more skilled, focused, and disciplined, as well as sportive. Training and development are systematically designed so that prospective e-sport athletes can obtain the right learning outcomes. The result of this program is the design of an e-sport curriculum that can educate people to become e-sport athletes who are disciplined, agile, responsible, trained, and purposeful.